Sport in people with tetraplegia: Review of recent literature - Tasiemski, Tomasz; Osińska, Monika (Akademia Wychowania Fizycznego w Poznaniu)
Sport participation in people with spinal cord injury (SCI) has been studied extensively, however there is little evidence available on sports for people with cervical SCI (tetraplegia). Due to physical consequences of cervical SCI people with tetraplegia have very limited possibility to engage in vigorous physical activity but increasing number of adaptive sports for people with tetraplegia allowed scientist to explore more intensively diverse aspects of sport participation in this population. The purpose of this review was to summarize the findings of recent studies related to sport in people with tetraplegia published in years: 2002-2013. A comprehensive search of computer databases was performed to identify relevant studies. These studies were grouped according to their subjects into five main areas of research involving athletes with tetraplegia:1) muscle strength and kinematics, 2) cardiovascular performance and functions, 3) thermoregulation system, 4) respiratory functions, and 5) social aspects of sport. Most of recent research into sport in people with tetraplegia is related to physiological body response to intensive physical training. Researchers do agree that adequately provided sport training in people with tetraplegia improves several physiological parameters such as peak power output or peak oxygen uptake. As biomedical aspects of sport in people with tetraplegia are already well documented in the literature it is suggested that future research should focus more on psychosocial aspect of this activity.Sport participation in people with spinal cord injury (SCI) has been studied extensively, however there is little evidence available on sports for people with cervical SCI (tetraplegia). Due to physical consequences of cervical SCI people with tetraplegia have very limited possibility to engage in vigorous physical activity but increasing number of adaptive sports for people with tetraplegia allowed scientist to explore more intensively diverse aspects of sport participation in this population. The purpose of this review was to summarize the findings of recent studies related to sport in people with tetraplegia published in years: 2002-2013. A comprehensive search of computer databases was performed to identify relevant studies. These studies were grouped according to their subjects into five main areas of research involving athletes with tetraplegia:1) muscle strength and kinematics, 2) cardiovascular performance and functions, 3) thermoregulation system, 4) respiratory functions, and 5) social aspects of sport. Most of recent research into sport in people with tetraplegia is related to physiological body response to intensive physical training. Researchers do agree that adequately provided sport training in people with tetraplegia improves several physiological parameters such as peak power output or peak oxygen uptake. As biomedical aspects of sport in people with tetraplegia are already well documented in the literature it is suggested that future research should focus more on psychosocial aspect of this activity.
Keywords: tetraplegia; quadriplegia; sport; wheelchair rugby; twin basketball; muscle strength and kinematics; cardiovascular performance and functions; thermoregulation system; respiratory functions; social aspects of sport